160 Modulation of Myocardial Ischaemic Injury by Carbon Monoxide Releasing Molecule-A1 in a Porcine Model of Acute Reperfusion Infarction. (3rd June 2016) - Alfaidi, Mabruka; Hughes, Matthew; Alizadeh, Tooba; Casbolt, Helen; Chamberlain, Janet; Mann, Brian E; Francis, Sheila E; Iqbal, Javaid; Gunn, Julian
Abstract : Introduction: Conventional pharmacological treatments for acute myocardial infarction (AMI), a life threatening complication of a sudden coronary occlusion, are limited by their efficiency and side effects. New therapeutic strategies are thus needed to improve outcomes. Carbon monoxide (CO) is cardio-protective at nanomolar concentrations. Carbon monoxide-releasing molecules (CORMs), capable of carrying and releasing controlled quantities of CO in cellular systems, are a promising therapeutic that overcome the limitations of CO gas. CORM-A1 is a water soluble and releases CO slowly through hydrolysis at physiological conditions. We investigated the efficacy and safety of CORM-A1 in reducing infarct size in a clinically relevant porcine model of re-perfused AMI. Methods: Male Yorkshire White pigs (25–33 kg) underwent a balloon-induced coronary occlusion at the middle segment of left anterior descending artery beyond the first diagonal branch for 60min. From 15min post-occlusion, sodium borate (control) or CORM-A1 (4.27 mM, each) were infused over a period of 60min. Left ventricular (LV) function and blood pressure were assessed by cardiac catheterization. Cardiac biomarkers, hepatic and renal functions were compared between the groups. Seven days after AMI, animals were culled and in-situ double staining with Evans blue and 2, 3, 5-triphenyltetrazolium (TTC) performed to measure infarct size. Myocardial inflammation, proliferation and apoptosis were evaluated by immunohistochemistry, immunoblotting, and TUNEL assay. Results: CORM-A1 treated pigs had a reduced infarcted area and improved LV function, but no significant change in blood pressure, compared to controls. Infarct size was 35 ± 7% of the area at risk (ischaemic area) in CORM-A1 pigs compared to 90 ± 5% in controls (p < 0.0001, n = 3–8/group). Myocardium from CORM-A1 treated animals had fewer TUNEL positive (30.5 ± 4.7 vs. 46.2 ± 6.6%, p < 0.05, n = 37), Ki67 positive (7.7 ± 2.3 vs. 29.0 ± 4.0%, p < 0.01, n = 3–7) and inflammation positive cells (4.3 ± 1.8 vs. 36.7 ± 7.1%, p < 0.01, n = 3–7) in the infarcted regions, compared to controls. CORM-A1 infused animals also had significantly reduced (2–3-fold) neovascular formation (vWF staining) in the infarcted areas compared to controls (22.0 ± 3.6 vs. 53.3 ± 8.9%, p < 0.01, n = 3–7). A similar pattern was seen in the ischaemic areas. These changes were associated with a down-regulation of HIF-1a expression in the myocardium of CORM-A1 treated animals. Conclusions: Our data suggest CORM-A1 as a key modulator of myocardial repair following re-perfused AMI injury. Injury is reduced in CORM-A1 treated animals by reducing inflammation, proliferation and cell death whilst maintaining healthy repair via neovascularisation. This study suggests the development of CORM-A1 as a potential new therapeutic for treatment of patients with AMI and warrants further clinical studies.